Two functions f and g are given. The solution for [tex]f(x)=g(x)[/tex] is -4.
Given:
The given functions are:
[tex]f(x)=-4x-3\\ g(x)=-3x+1[/tex]
It is required to get the value of x for which f(x) is equal to g(x).
So, the value of x can be calculated as,
[tex]f(x)=g(x)\\ -4x-3=-3x+1\\ -x=4\\ x=-4[/tex]
So, at [tex]x=-4[/tex] the functions will be equal.
Therefore, the solution for [tex]f(x)=g(x)[/tex] is -4.
For more details about functions, refer to the link:
https://brainly.com/question/5245372